2021
DOI: 10.1007/s40519-021-01162-z
|View full text |Cite
|
Sign up to set email alerts
|

An update on the prevalence of eating disorders in the general population: a systematic review and meta-analysis

Abstract: Objective To update the prevalence of eating disorders in the general population before 2021 and to analyze the distribution characteristics at different times and in different regions and sexes, as well as the diagnostic criteria. Methods Based on the method from a previous report by the authors, studies were identified from the following databases: PubMed/Medline, PsycINFO, ISI Web of Knowledge, Ovid and the 4 most important Chinese databases. Articles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(191 citation statements)
references
References 36 publications
11
174
2
4
Order By: Relevance
“…In fact, overweight or obese women have a significantly higher rate of food addiction compared to men [29]. is confirms the fact that eating disorders are more common among women than men [32]. However, larger studies in different populations are suggested to confirm the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, overweight or obese women have a significantly higher rate of food addiction compared to men [29]. is confirms the fact that eating disorders are more common among women than men [32]. However, larger studies in different populations are suggested to confirm the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Several different assessment tools that aim to measure Caregiver Burden (CB) are available internationally, among which the Caregiver Burden Inventory (CBI) is probably Introduction Eating Disorders (EDs) are complex mental disorders de ned by disturbed eating behaviours, distorted beliefs, and extreme concerns about food, eating and body image, shape or weight. The prevalence of these conditions is rising in many countries and recent studies suggest that EDs are not rare in the general population [1,2]. Their association with decreased quality of life, increased risk of depression and substance abuse has been shown in several studies [1].…”
Section: Plain English Summarymentioning
confidence: 99%
“…Eating disorders can be categorized into a class of mental illnesses that could result in numerous somatic and psychiatric complications and have penchant to perturb living quality as well as mortality in some cases. This psychiatric condition has increasingly been able to seek attention among world health fraternities over the past 20 years [1]. In accordance with the National Eating Disorder Association, not less than 70 million people across the world including both the male and female have been reported to experience eating disorders during their lifetime [2].…”
Section: Introductionmentioning
confidence: 99%